Design and efficacy of an Ecohealth competency-based course on the prevention and control of vector diseases in Latin America. - Magaña-Valladares, Laura; Rodríguez, Mario Henry; Betanzos-Reyes, Ángel Francisco; Riojas-Rodríguez, Horacio; Quezada-Jiménez, María Laura; Suárez-Conejero, Juana Elvira; Lamadrid-Figueroa, Héctor (Salud Pública de México)
Objective. To design and analyze the efficacy of an Ecohealth competency-based course on the prevention and control of vector-borne-diseases for specific stakeholders. Materials and methods. Multiple stakeholders and sectors of the region were consulted to identify Ecohealth group-specific competencies using an adjusted analysis matrix. Eight courses based on the competencies were implemented to train EA tutors. The effectiveness of the course was evaluated through the use of paired- t-tests by intervention group. Results. Strategic, tactical, academia and community stakeholder groups and their competencies were identified. An overall gain of 43 percentage points (p<0.001) was observed in terms of competencies score in trained tutors, which further trained 1 033 people. Conclusion. The identification of the stakeholders and their competencies proved to be useful to guide training courses to significantly improve the initial competencies and create a critical mass to further advance the EA in the region.